2016
DOI: 10.1039/c6cp01387b
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation capacity and natural payload delivery of an anticancer drug from boron nitride nanotube

Abstract: The behavior of confined anticancer carboplatin (CPT) molecules in a single (10, 10) boron nitride nanotube (BNNT) was studied by means of molecular dynamics simulations. Our study revealed a very large storage capacity of BNNT. Analysis of the energy profiles depending on the number of confined molecules, and on their spatial organization allowed us to quantify the ability of BNNT to vectorize CPT. Indeed, BNNT despite its small radius presented a large inner volume that favored stable encapsulation of multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 43 publications
1
31
1
Order By: Relevance
“…Both cell viability and apoptosis data indicate that the purification of BNNTs in dispersed or nondispersed form reduces their cytotoxicity compared to nonpurified BNNTs. Next, we determined the hydrophobic drug encapsulation ability, as both CNTs and BNNTs have potential applications as drug carriers [38,39]. Hydrophobic anticancer small molecule CPT was used to test encapsulation efficiency of BNNTs and pBNNTs.…”
Section: Discussionmentioning
confidence: 99%
“…Both cell viability and apoptosis data indicate that the purification of BNNTs in dispersed or nondispersed form reduces their cytotoxicity compared to nonpurified BNNTs. Next, we determined the hydrophobic drug encapsulation ability, as both CNTs and BNNTs have potential applications as drug carriers [38,39]. Hydrophobic anticancer small molecule CPT was used to test encapsulation efficiency of BNNTs and pBNNTs.…”
Section: Discussionmentioning
confidence: 99%
“…This diffusion process was energetically favorable to the system due to the contribution of different energy component combinations. According to these results, the possibility of BNNT-OH as a specific ligand for cancer cells allows the more precise encapsulated drug delivery in cell membranes [85]. Table 1.…”
Section: Computational Simulation Perspectives Of Boron Nitride Nanotmentioning
confidence: 87%
“…These theoretical results showed that the therapeutic Pt (IV) complex was not affected when it was attached onto BNNTs [84]. In another work, Khalifi et al also demonstrated theoretical results about the use of BNNT particles as carrying drug insertion into to the lipid bilayer [85]. They studied a single-walled BNNT armchair (10,10) with diameter 13.94 Å and length 21.32 Å (also saturated with -OH groups) with its extremities encapsulated with carboplatin (CPt) in ionized solvated ambient to mimic a biological environment.…”
Section: Computational Simulation Perspectives Of Boron Nitride Nanotmentioning
confidence: 92%
See 1 more Smart Citation
“…The quality and the control of the inner part of the nanopore could thus be managed and could yield to the creation of biomimetic nanopore when ionic channel will be translocated inside the nanopore. We can also imagine that the new biomimetic channel developed in this way could be used as a future cargo to transport the encapsulated drug until its target in order to repair or to ameliorate the current medical treatments [28][29][30][31]. The development of high performing calculations allows now to study in global realistic view any system and to predict in a relatively low error the behavior of complex system.…”
Section: Introductionmentioning
confidence: 99%